On‐line equalization for lithium iron phosphate battery packs based on voltage threshold integral. (8th September 2022) - Qian, Guangjun; Zheng, Yuejiu; Lu, Yufang; Han, Xuebing; Sun, Yuedong; Chen, Yingjie
Summary: Dissipative equalization is a feasible on‐line equalization method in the battery management system (BMS). However, equalization strategies based on remaining charging capacity (RCC) consistency largely ignore the broader stability and scalability issues that may arise in practical BMS applications, and no explicit methods have been proposed to address these problems. Therefore, this study provides a novel based on the RCC consistency voltage threshold integral method and reveals that the essence of dissipative equalization is to estimate the target equalization capacity (TEC). This part used an integrated approach to estimate the TEC to make the whole algorithm more scalable. Moreover, a dynamic iteration method is proposed for the equalization switching control strategy to ensure a steady equalization process. Finally, the effectiveness of the proposed algorithm is demonstrated by verifying and comparing the battery pack capacity with/without the equalization algorithm using the battery pack model with different consistencies and charging strategies. The result shows that this strategy could achieve a high‐capacity utilization rate (above 98%) of the battery pack and has the potential to be used in real BMS for on‐line equalization. Abstract : This study provides a novel based on the RCC consistency voltage threshold integral method and reveals that the essence of dissipative equalization is to estimate the target equalization capacity (TEC). This part used an approach of integral to estimate the TEC in order to make the whole algorithm more scalable. Moreover, a dynamic iteration method is proposed for the equalization switching control strategy to ensure a steady equalization process.